2017
DOI: 10.3945/ajcn.117.153858
|View full text |Cite
|
Sign up to set email alerts
|

Trends in added sugars from packaged beverages available and purchased by US households, 2007–2012

Abstract: The US Food and Drug Administration's updated nutrition labeling requirements will include added sugars starting in July 2018, but no measure currently exists to identify the added sugar content of products and what it represents among purchases. Beverages are one of the first targets for reducing added sugar consumption, and hence are the focus here. Our goal was to estimate trends in added sugars in nonalcoholic packaged beverage products available in the United States and to estimate amounts of added sugars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
4
11
1
Order By: Relevance
“…Moreover, the consumption proportions of ≥3 times/week among the four surveyed sugar-sweetened beverages (SSBs) was consistent with results of one previous study, which showed that vegetable/fruit-flavoured drinks and tea beverage had become the leading SSBs in China [39]. With increasing studies and rapid spread of mass media, the public has improved the awareness of the high sugar content and hazards of carbonated SSBs (CSSBs) [40,41]. Thus, some people prefer non-carbonated SSBs (NCSSBs) as potential alternatives to CSSBs with the perception that they are healthier [42].…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the consumption proportions of ≥3 times/week among the four surveyed sugar-sweetened beverages (SSBs) was consistent with results of one previous study, which showed that vegetable/fruit-flavoured drinks and tea beverage had become the leading SSBs in China [39]. With increasing studies and rapid spread of mass media, the public has improved the awareness of the high sugar content and hazards of carbonated SSBs (CSSBs) [40,41]. Thus, some people prefer non-carbonated SSBs (NCSSBs) as potential alternatives to CSSBs with the perception that they are healthier [42].…”
Section: Discussionsupporting
confidence: 85%
“…Thirty-four studies were included in this scoping review [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Information on customer purchasing assessment methodologies used across studies is shown in ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies (44.1%) examined purchasing outcomes across racial and/or ethnic groups [ 27 , 29 , 30 , 39 , 42 , 43 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 53 , 54 ]. All studies examined purchasing among NHW, 14 examined purchasing among NHB, 14 studied purchasing among Hispanic, nine examined purchasing among non-Hispanic Other (or a different author definition that collapsed multiple racial/ethnic groups), and three investigated purchasing among Asian (using the author definition).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, Central and South American countries are the principal producers of tropical beverage crops, fruits, and sugar [30] (Table 1). Additionally, consumer-wise, there has been a shift from nutrient-deficient, added-sugar and high fructose-containing beverages to more natural fruits and herbal infusions due to the prevalence of obesity [31,32]. Natural fruit juice drinking has changed the dynamics of the still drinks industry and consumption patterns.…”
Section: Consumption Data For Tropical Beverages and Related Productsmentioning
confidence: 99%